Obtaining of hybrid nanocomposites by simultaneous photopolymerization of some urethane monomers and photoinduced formation of gold nanoparticles. Issue 5 (18th December 2013) - Chibac, Andreea L.; Melinte, Violeta; Buruiana, Tinca; Buruiana, Emil C.
ABSTRACT Urethane–urea dimethacrylates were synthesized and used in the preparation of nanocomposites containing gold nanoparticles (Au NPs) in situ photogenerated during the UV‐curing process in the absence of reducing agent. A study of the photopolymerization kinetics showed that the photoreactivity of the monomers alone or in combination with a dual urethane benzophenone (BP) macromer is dependent on the nature of photoinitiator (Irgacure819, BP/amine) and the formulation composition. It was found that the addition of 1 wt % AuBr3 in monomers slightly improved the polymerization rate and the degree of conversion. The formation of Au NPs into the network was confirmed through UV–vis, XRD, EDX, SAXS, and TEM analyses, the last indicating the existence of NPs with size around 8.5 nm and spherical/triangle shapes. On addition of 10 wt % 2[N‐methacryloyloxyethyl‐(N'‐2‐thioethyl)] (urea) in formulation, the Au NPs (200 nm) became predominantly cubic/hexagonal in shape. The composite films emit fluorescence at 575 nm, and this property could be exploited in the field of fluorescent bio/sensors. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 728–738